IMPROVE CRITICAL THINKING STUDENTS IN INDONESIA FOR NEW LEARNING MANAGEMENT SYSTEM - Iqbal Desam Girinzio; Ahmad Ramadan; Dimas Bagus Saputra; Gadis Mustika; Sulistio (International Transactions on Education Technology (ITEE), 2023)
In Indonesian 4.0's goal for a knowledge-based economy, critical thinking skills have been given more weight. Given the seriousness of the problem, the researchers gathered a focus group of nine professionals in August 2017 and asked them to help create a new critical thinking education methodology. From this, the authors developed the "PUSCU Model," a five-focus management paradigm. Two subgroups of 69 students were formed using random cluster sampling. Two groups: one with 34 participants in traditional learning and one with 35 participants in experimental investigations. From November 2016 to February 2017, a 16-week test of the PUSCU model was carried out. A single Multivariate Analysis of Variance (MANOVA) was performed using the Statistical Package for the Sciences (SPSS) 21 software to ascertain any differences between the experimental and control groups. The outcomes showed that the study group's participants were content with the instructor's usage of the created learning materials and that, on the whole, they performed well in terms of critical thinking skills and academic performance.